2000
DOI: 10.1210/jcem.85.10.6860
|View full text |Cite
|
Sign up to set email alerts
|

The A19G Polymorphism in the 5′ Untranslated Region of the Human Obese Gene Does Not Affect Leptin Levels in Severely Obese Patients

Abstract: Recently, the presence of different polymorphisms in the regulatory region of the ob gene has been associated with variations in leptin levels. However, the results of these studies are still contradictory. The aim of the present investigation was to evaluate the presence of the A19G polymorphism in an Italian population of obese patients and to verify its association with leptin levels and anthropometric, metabolic, and clinical parameters. Two hundred five obese patients [body mass index (BMI) > 36 kg/m2; 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
13
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 12 publications
4
13
0
2
Order By: Relevance
“…Using LEP 19GG as the referent group, the recalculated FL risk estimate for the LEP 19AA genotype is 0.6 (95% CI 0.3 -1.3), similar to the OR of 0.5 (95% CI 0.3 -0.8) presented here. As has been observed elsewhere, the BMIs of our controls were not correlated with LEP 19G4A (r ¼ 0.014, P ¼ 0.70) (Karvonen et al, 1998;Lucantoni et al, 2000), LEP À2548G4A (r ¼ À0.013, P ¼ 0.72) (Mammes et al, 1998;Le Stunff et al, 2000), LEPR 223Q4R (r ¼ À0.008, P ¼ 0.83) (Gotoda et al, 1997;Rosmond et al, 2000;Wauters et al, 2001) or APM1 276G4T (r ¼ À0.024, P ¼ 0.51) (Menzaghi et al, 2002;Fumeron et al, 2004). Moreover, this and the previous report by Skibola et al found little evidence that risks associated with BMI varied by genotype.…”
Section: Discussionsupporting
confidence: 76%
“…Using LEP 19GG as the referent group, the recalculated FL risk estimate for the LEP 19AA genotype is 0.6 (95% CI 0.3 -1.3), similar to the OR of 0.5 (95% CI 0.3 -0.8) presented here. As has been observed elsewhere, the BMIs of our controls were not correlated with LEP 19G4A (r ¼ 0.014, P ¼ 0.70) (Karvonen et al, 1998;Lucantoni et al, 2000), LEP À2548G4A (r ¼ À0.013, P ¼ 0.72) (Mammes et al, 1998;Le Stunff et al, 2000), LEPR 223Q4R (r ¼ À0.008, P ¼ 0.83) (Gotoda et al, 1997;Rosmond et al, 2000;Wauters et al, 2001) or APM1 276G4T (r ¼ À0.024, P ¼ 0.51) (Menzaghi et al, 2002;Fumeron et al, 2004). Moreover, this and the previous report by Skibola et al found little evidence that risks associated with BMI varied by genotype.…”
Section: Discussionsupporting
confidence: 76%
“…The lower RQ might suggest that this genotype combination results in a more efficient leptin-leptin receptor signaling compared to the other genotypes. We found no associations between the 19A4G LEP variant and RMR or RQ, which is in agreement with findings in an Italian 48 and a Finnish 40 obese population. Obese individuals who carry the A19 allele showed significantly higher leptin concentrations compared to obese patients who were G19G homozygotes.…”
supporting
confidence: 92%
“…As for G2548A, the frequency of the G allele observed in our sample was higher (0.67 vs. 0.41-0.60) than those reported for Tunisian [13] and especially for Turkish [12] and Iraqi [24] populations. Conversely, the frequencies for A19G were very similar to those reported for healthy patients worldwide, including Italy [25], other European countries [26,27], Tunisia [13] and the United States [15]. …”
Section: Discussionsupporting
confidence: 71%